1986
DOI: 10.1530/jrf.0.0770265
|View full text |Cite
|
Sign up to set email alerts
|

Interstrain competition amongst mouse spermatozoa inseminated in various proportions, as affected by the genotype of the Y chromosome

Abstract: Nonagouti (KP X C57BL)F1 hybrid females were artificially inseminated with a mixture of spermatozoa from males of the KE (nonagouti) and CBA (agouti) strains and the genotype of young was estimated by fur pigmentation. When KE and CBA spermatozoa mixed in the ratios of 1:1, 2:1 and 4:1 were inseminated after ovulation, 87%, 56% and 29% of progeny, respectively, were sired by CBA males, i.e. proportions of CBA progeny were significantly higher than ratios of CBA spermatozoa in the mixture. The surplus of CBA pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…The time of insemination relative to ovulation is crucial for the success of fertilization (Krzanowska, 1986;Gomendio et al, 1998). Thus, it is expected that spermatozoa that become ready to interact with the ovum faster (i.e.…”
Section: Pkdrej As Target Of Sexual Selection In Rodentsmentioning
confidence: 99%
“…The time of insemination relative to ovulation is crucial for the success of fertilization (Krzanowska, 1986;Gomendio et al, 1998). Thus, it is expected that spermatozoa that become ready to interact with the ovum faster (i.e.…”
Section: Pkdrej As Target Of Sexual Selection In Rodentsmentioning
confidence: 99%
“…The observation of differences in fertilization kinetics of the two strains used in this study and other strains [3,6,[20][21][22][23] prompted us to study the maternal and paternal effects on fertilization and subsequent developmental k i n e t i cs i n v i t r o b y c o n d u c t i n g cr o s sb r e e d i n g experiments of these two inbred strains of mice.…”
Section: Discussionmentioning
confidence: 99%
“…This number of ovulations is quite high when At each time point, values with different superscripted letters in the same column are significantly different (P<0.05). [3,6,[20][21][22][23] have shown the involvement of genetic factors in not only fertilization competence but also fertilization kinetics in vitro as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments performed in the Department of Genetics and Evolution of the Jagiellonian University conducted by Krzanowska and her coworkers on inbred strains of mice, which differed in the level of sperm abnormalities and efficiency of fertilization, showed that the source of the Y chromosome plays a significant role in the inheritance of these traits and possibly contains genes controlling the course of spermatogenesis (Krzanowska, 1969;Krzanowska, 1972b;Krzanowska, 1986). This was confirmed later by the finding of an increased level of sperm abnormalities in males with a partial deletion of the Y chromosome (Styrna et al, 1991).…”
mentioning
confidence: 99%